Climate Change, Flood Disaster Risk and Food Security Nexus in Northern Ghana - Atanga, Raphael Ane; Tankpa, Vitus (Frontiers in Sustainable Food Systems, 2021)
This research reviews climate change, flood disasters impacts and food security nexus in northern Ghana. The impacts of climate change include flood disasters which in turn affect food production with subsequent impact on food security. While climate change impact can be positive in some regions, it can be negative in other regions as it could lead to excess or lack of water, which negatively affects food production. Most especially, flood disasters have reportedly become frequent with devastating consequences on food production. Literature further suggests that the frequency of floods and their impacts have the potential to increase in the future. Floods inundate farms, pastures and livestock, which could subsequently reduce crop yields and animal production. Floods also destroys physical infrastructure and disrupts socio-economic activities which are linked to agriculture sector and could affect food production. This eventually decreases food availability, accessibility, utilisation and stability in the region. Northern Ghana has experienced flood disasters with increased frequency, which are related to climate change impacts. Although there is research on climate change, flood disasters, and food security issues in northern Ghana, the literature thus far indicates no clear focus of studies that focuses on the nexus of climate change, flood disasters and food security of the study site. Thus, this research reviewed the nexus of climate change, and flood disaster impacts on food security in northern Ghana with their implications on food security in the region. This study has two main research objectives. The first objective is to identify and understand the potential impacts of climate change and flood disasters on food production in the study site. The second objective is to explain the connection between climate change and flood disasters and the implications of this relationship on food security in the study site. This review study focuses on climate change, flood disasters and food production to understand the critical impacts of climate change and flood disasters on food security in the northern part of Ghana. The aim of this research is to contribute to literature and discussion of the nexus of climate change, flood disaster impacts and food security sub-Saharan Africa.